2016
DOI: 10.1123/ijsnem.2015-0337
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Weight-Bearing Training and Anti-MSTN Polyclonal Antibody Improve Bone Quality In Rats

Abstract: Weight-bearing exercise is beneficial to bone health. Myostatin (MSTN) deficiency has a positive effect on bone formation. We wondered if a combination of weight-bearing training and polyclonal antibody for MSTN (MsAb) would augment bone formation to a greater degree than single treatment. In this study, rats were randomly assigned to four groups: Control, weight-bearing training (WT), MsAb, and WT+MsAb. The trained rats ran at 15 m/min bearing with 35% of their body weight, 40 min/day (2 min of running follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Total RNA was isolated using TRIzol reagents (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) according to the manufacturer's instructions, and then it was reverse-transcribed using a PrimeScript™ II 1st Strand cDNA Synthesis kit (Takara Shuzo, Shiga, Japan) (19). Briefly, the RNA with 2 µg was added to 12 µl reaction system of reverse transcription (including 1 µl oligo(dT) 18 ) and then placed in PCR amplifier at 70˚C for 5 min. Then the above system was added in order 4 µl 5xbuffer, 2 µl 10 mM dNTPs, 1 µl RNA inhibitor and 1 µl reverse transcriptase and placed in PCR amplifier at 42˚C for 60 min, the reaction was ended at 80˚C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated using TRIzol reagents (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) according to the manufacturer's instructions, and then it was reverse-transcribed using a PrimeScript™ II 1st Strand cDNA Synthesis kit (Takara Shuzo, Shiga, Japan) (19). Briefly, the RNA with 2 µg was added to 12 µl reaction system of reverse transcription (including 1 µl oligo(dT) 18 ) and then placed in PCR amplifier at 70˚C for 5 min. Then the above system was added in order 4 µl 5xbuffer, 2 µl 10 mM dNTPs, 1 µl RNA inhibitor and 1 µl reverse transcriptase and placed in PCR amplifier at 42˚C for 60 min, the reaction was ended at 80˚C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it plays a role in regulating bone mass (16). Our previous studies showed that ladder-climbing training could prevent bone loss in diet-induced obese rats by inhibiting MSTN expression (17,18); meanwhile, MSTN is not expressed and secreted in osteoblasts. Active MSTN binds to ActRIIB and could lead to the subsequent phosphorylation of Smad proteins and the initiation of gene expression, so we wondered if exercise could modulate bone metabolism in streptozocin (STZ)-induced diabetes through the inhibition of MSTN.…”
Section: Introductionmentioning
confidence: 99%
“…To generate a more intense exercise and/or load, the principle of weight bearing was applied on the vertebrae of animals. A backpack, representing up to 20% of body weight of the animal tested, was used during the whole running session [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Effects Of Physical Exercises On Bone Health Statusmentioning
confidence: 99%
“…78 Antimyostatin antibodies Antimyostatin antibody in combination with resistance exercise improved bone health in rats. 79 (1) Antimyostatin antibodies increased muscle mass and strength in mice. 80 (2) Antimyostatin antibodies increased lean mass and may improve functional measures of muscle power.…”
Section: Pharmacological Agent Osteoporosis Sarcopeniamentioning
confidence: 99%
“…80 In phase II trials in older adults (aged ⩾75 years) with a history of fall, antimyostatin antibodies increased the lean body mass and mildly improved functional measures associated with muscle strength. 81 Regarding role of myostatin antibodies in improving bone health, data from animal studies indicate that in combination with resistant exercise, myostatin antibodies improved bone mass, 79 however, this effect has not been confirmed in clinical trials.…”
Section: Pharmacological Management Of Osteosarcopeniamentioning
confidence: 99%